Heavy Metal Removal from Wastewater Using Synthesized Silicate-1 Nanocrystal - Muhammad, Syaifullah; Syahputra, Edy; Nasrullah, Nasrullah; Suraiya, Suraiya; Wang, Shaobin; Tade, Moses O. (Jurnal Rekayasa Kimia & Lingkungan, 2011)
Particle size reduction of zeolite to the nanometer scale leads to substantial changes in the properties of zeolite which make them promising materials for many applications including adsorption. Zeolite silicate-1 Nanocrystal was synthesized at temperatures of 800C, 1200C and 1500C by adding tetrapropylammonium hydroxide (TPAOH) into silica sources. The synthesis mixtures are 2TPAOH: 0.15Na2O: 4.5Si: 382H2O: 51EtOH (TEOS as silica source) and 2TPAOH: 0.15Na2O: 6SiO2: 532H2O: 51EtOH (Ludox LS as silica source). X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) were used to characterize the synthesised products. The nanosilicate-1 particle size were obtained in range of 119 nm 1678 nm. This research also confirmed that TEOS can make smaller particle size up to 36.43 % than Ludox LS due to an average hydrodynamic diameter of 4 nm of TEOS smaller than Ludox LS of 15-19 nm. In the heavy metal adsorption study, it was found that the adsorption capacity indicated by Qmax (Langmuir) and KF (Freundlic) shows higher Pb2+ adsorption than Cr3+. The maximum adsorption capacities of Pb and Cr at 300C are 131.58 mg/g and 129.87 mg/g, respectively. Further, it can also be seen that the KL values in the Langmuir isotherm indicate the higher selectivity of Pb on silicate-1 zeolite than Cr.Keywords :Adsorption capacity, Heavy metal, Isotherm, Silicate-1 nanocrystal